Effects of wrist wraps on throwing distance in highly skilled shot put athletes - Judge, L. W.; Burke, J. M.; Patrick, T. J.; Guidry, T. D.; Hoover, D. L.; Wanless, E. A.; Bellar, D. M. (International Journal of Performance Analysis in Sport, 2015)
Shot put throwing distances of 18 male Division I track and field athletes in the United States were compared among three wrist wrap conditions: 1) a large heavy wrist wrap, typically worn by athletes competing in the shot put event, 2) a small light wrist wrap and 3) no wrist wrap. The average and maximum throwing distances when the athletes were wearing the heavy wrist wrap (12.31 ± 1.699maximum; 11.92 ± 1.627average) were greater than when the athletes were not wearing a wrist wrap (12.05 ± 1.550maximum; 11.70 ± 1.457average). Performance increases exceeded criteria for the smallest worthwhile improvements in the shot put event, suggesting that heavy wrist wraps provide a competitive advantage. These results revealed previously undocumented, beneficial effects of taping and bracing on sports performance in the shot put throw.